Comparison of biological activity of phenolic fraction from roots of Alhagi maurorum with properties of commercial phenolic extracts and resveratrol. (17th November 2015) - Olas, Beata; Hamed, Arafa I.; Oleszek, Wieslaw; Stochmal, Anna
Abstract: Phenolic compounds have different biological properties, including antioxidative activities, but they may also be prooxidants. The effect of phenolic fraction from roots of Alhagi maurorum on oxidative protein/lipid damages (determined by such parameters as levels of protein thiol groups and the concentration of thiobarbituric acid reactive species – TBARS) in human blood platelets and human plasma after treatment with hydrogen peroxide – H2 O2 (which is the strong biologic oxidant and inflammatory mediator) was studied in vitro. We also studied the effect of A. maurorum extract on blood platelet activation corresponding to thrombin-induced arachidonic acid pathway. Moreover, the present work was designed to study the effect of A. maurorum extract on selected physiological function of blood platelets – adhesion of blood platelets to collagen in vitro . The action of phenolic fraction from A. maurorum was compared with the selected commercial phenolic extracts: extract from berries of Aronia melanocarpa (Aronox® ), extract from bark of Yucca schidigera and monomeric polyphenol–resveratrol (3, 4′, 5-trihydroxystilbene). Exposure of blood platelets or plasma to H2 O2 resulted in a decrease of the level of thiol groups in proteins, and an increase of TBARS. In the presence of phenolic fraction from A. maurorum (0.5–50 µg/ml), a reduction of thiol groups oxidation together with the decrease of autoperoxidation of lipids and lipid peroxidation caused by H2 O2 or thrombin was observed. The inhibitory, concentration-dependent effects of A. maurorum extract on adhesion of thrombin-activated platelets to collagen were also found. The phenolic fraction from A. maurorum acts as an antioxidant and can be useful as the natural factor protecting against diseases associated with oxidative stress. Tested fraction from A. maurorum has more effective antioxidative activity and antiplatelet properties than aronia extract or other commercial extract, however differences between their actions are not statistically significant.